Placentární a pupecníkové zmĕny u zen závislých na tvrdých drogách - Vavrinková, B; Binder, T; Vítková, I; Zivný, J (Ceska gynekologie, 2001)
OBJECTIVE: The aim of the study was to gauge the impact of drugs on placental changes in heroin and pervitin addict pregnant women as one of the influence factors supporting the lower birth-weight of the neonate. DESIGN OF THE STUDY: Prospective study. SETTING: The Department of Gynaecology and Obstetrics and the Department of Pathology of the General Teaching Hospital and the 1st Medical Faculty of Charles University in Prague. METHODS: The drugs-addict pregnant women were included in the study in the period between January 1998 till the end of the year 2000. We succeeded to concentrate in total 39 drug abused pregnant women and 39 their placentas and umbilical cords were examined (19 heroin and 20 pervitin addict). The placentas were sent for the histological examination in total without the chemical fixation. There were 3 placental samples, 2 cord and 2 membranes samples examined. The controls groups were formed by non-abused pregnant women and their placentas by method of accidental choice. RESULTS: We found the statistically significant higher incidence of placental and cords abnormalities in among the addict women compared to their non abused controls (P < 0.05). In heroin addict group in 16 from 19 cases were the abnormalities present. We registrated increased intervillous and perivillous microfibrin deposits (6 times), an increased number of trophoblastic proliferation buds (7 times) increased vascularization of the villi (7 times) mikrovilli (6 times) and their necrosis (5 times). In umbilical cord we enregistered in 3 cases the only one artery, in two case the thrombosis of the vein. In 5 cases we also found the signs of infection. In pervitin addict group we registered placental changes in 9 from 20 cases. The majority of them presented as increased microfibrin deposits on the surface and also in the choriotic board (9 times), in five cases we enregistered the intervillous haemorrhage manifested in 2 cases clinically as abruption of placenta. The placental changes participate in low birth weight of neonates, IUGR and the abbreviation of the gestational duration. CONCLUSION: The microscopic changes in placenta is the expression of the circulatory disorder during the attack of the drug. They are not four-square specific, rather quantitatively expressed. In heroin abused women is the incidence of placental changes much more higher comparing to pervitin-addict. Heroin led more frequently to preterm labour, lower birth-weight and IUGR. The pervitin-addict mothers are higher risk of placental abruption.
Keywords: závislost na heroinu; pupečník; Heroin Dependence; výsledek těhotenství; Pregnancy; Humans; Placenta; Female; Pregnancy Outcome; lidé; Pregnancy Complications; Umbilical Cord; methamfetamin; poruchy spojené s užíváním amfetaminu; Amphetamine-Related Disorders; ženské pohlaví; těhotenství; komplikace těhotenství; placenta; prospektivní studie; Methamphetamine; Prospective Studies